Spacial Factors of Craft Breweries Business Performance - Sůvová, Kristýna; Sabolovič, Mojmír, 1978-; Kšír, Otakar; Vysoká škola ekonomická v Praze. Fakulta managementu (2024)
Aim of this thesis is to introduce a list of spatial and additional factors and examine their influence on the business performance of microbreweries (with production of up to 10 000 hl of beer per year) in the Czech Republic. Six factors are considered including population of the brewery’s region, demographics, regional GDP, location in or out of the capital, size and age of business. Multiple regression analysis is performed with numerically expressed factors as independent variable. Business performance is expressed using Kralicek’s Quicktest and Altman’s Z-Score model. Results show the influence of the firm size and age of business. The thesis brings new light on the importance of spatial and additional factors in the microbrewing industry.
Vedoucí práce: Mojmír Sabolovič
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor bakal. práce]; bakalářské práce; bachelor's theses